(untitled) (Journal of Student Affairs in Africa, 2021)
This issue comes at a time when the world is in the grip of the Corona virus pandemic and on lockdown, and when there is a worldwide outrage over the continuous violation of black bodies and the injustice and inhumanity inherent in systems and practices steeped in racism. The corona virus and its impact on higher education, on students and Student Affairs and Services, and the devastating impact of racism in higher education and the student experience and the work it involves for Student Affairs and Services are the themes of this editorial.